اتجاهات الطلبة في كلية دراسات اللغات الرئيسية نحو تعلم البلاغة العربية عبر برنامج الوسائط المتعددة = Ittijahat al-talabah fi kuliyyah dirasat al-lughat al-ra'isiyyah nahwa ta'allum al-balaghah al-arabiyyah abra barnamij al-wasa'it al-muta'addidah - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri; Nasir, Mohd Shahrizal (Fakulti Pengajian Kontemporari Islam, Universiti Sultan Zainal Abidin, 2016)
This study discusses in details the practical steps concerning the development of multimedia program for teaching Arabic Rhetoric. 160 third year students from Fakulti Pengajian Bahasa Utama, Universiti Sains Islam Malaysia had participated in the study which was carried out during the semester two of 2014/2015 academic year. After the end of the development process, a pilot study was used to confirm if the multimedia program for teaching Arabic Rhetoric is ready for full-scale implementation. An informal interview (thinkaloud method) has been conducted with the students during the process of learning Arabic Rhetoric. The outcome of the interview proposed the use multimedia program as a tool is for enhancing their desires in learning Arabic Rhetoric as they are found to be highly motivated and engaged in the learning process.